Wealth, power, and prestige : emerging patterns of social inequality in a peasant context - Hettige, S. T. (Siripala T.) (Colombo, Sri Lanka : Ministry of Higher Education, 1984)
Study relates to a village in north-central Sri Lanka.
Includes index.
Keywords: Sri Lanka -- Rural conditions -- Case studies